2013
DOI: 10.1089/thy.2012.0560
|View full text |Cite
|
Sign up to set email alerts
|

CD3CD16CD56brightImmunoregulatory NK Cells are Increased in the Tumor Microenvironment and Inversely Correlate with Advanced Stages in Patients with Papillary Thyroid Cancer

Abstract: CD3(-)CD16(-)CD56(bright) NK cell infiltration seems to be associated with PTC progression. These findings contribute to a better understanding of the immune response in PTC and may lead to novel immunotherapeutic approaches in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 53 publications
3
56
0
Order By: Relevance
“…Previous studies which have examined NK cells in the context of tumor development have described these cells as non-functional due to their lack of activation markers and increased expression of inhibitory receptors 12,[26][27][28] . In the context of our work, we believe that these cells are not necessarily nonfunctional but are at a different stage in their development within tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies which have examined NK cells in the context of tumor development have described these cells as non-functional due to their lack of activation markers and increased expression of inhibitory receptors 12,[26][27][28] . In the context of our work, we believe that these cells are not necessarily nonfunctional but are at a different stage in their development within tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the percentage of CD56 dim NK cells was lower in the tumor than in in peripheral blood. Gogali and colleagues have recently reported that in patients with PTC, CD56 dim NK cells were lower in PTC tissue than in peripheral blood, although the ratio of CD56 dim NK cells in the PTC-infiltrating NK cell population correlated positively with disease stage (38). There are several possible explanations for the skewed ratio between CD56 bright and CD56 dim NK cells in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These studies provide insights on how BRAF V600E mutant determines cancer initiation, progression, and invasiveness in PTCs and may provide new therapeutic targets for the treatment of aggressive PTCs (Bommarito et al 2011). CD3KCD16KCD56bright immunoregulatory NK cells are increased in the tumor microenvironment and were found to be inversely correlated with advanced stages in patients with PTC (Gogali et al 2013). In a recent analysis of four new ATC cell lines, Marlow et al (2010) have reported that suppressed RHOB was implicated as a molecular target for the treatment of ATCs, because drugs like romidepsin, a histone deacetylase inhibitor, was able to inhibit cell proliferation and upregulate RHOB in these new ATC cell lines.…”
Section: Role Of the Microenvironmentmentioning
confidence: 95%